Program comprehension through reverse‐engineered sequence diagrams: A systematic review. Issue 11 (25th July 2018) - Ghaleb, Taher Ahmed; Alturki, Musab A.; Aljasser, Khalid
Abstract: Reverse engineering of sequence diagrams refers to the process of extracting meaningful information about the behavior of software systems in the form of appropriately generated sequence diagrams. This process has become a practical method for retrieving the behavior of software systems, primarily those with inadequate documentation. Various approaches have been proposed in the literature to produce from a given system a series of interactions that can be used for different purposes. The reason for such diversity of approaches is the need to offer sequence diagrams that can cater for the users' specific goals and needs, which can vary widely depending on the users' perception and understandability of visual representations and the target application domains. In this paper, we systematically review existing techniques in this context while focusing on their distinct purposes and potentials of providing more understandable sequence diagrams. In addition, a qualitative evaluation of such techniques is conducted to expose their adequacy and applicability for effective program comprehension. Finally, we list a set of possible extensions to theunified modeling language sequence diagram standard that we anticipate will enhance its versatility and understandability of program control flow, followed by a number of concluding remarks.